Growth and flowering of ornamental pot plants influenced by growing media – A review - THAKUR , TANYA; GARG, ARUSHI (Journal of Ornamental Horticulture, 2025)
This review presents an overview of various growing media and their compositions for enhancing morphological development and flowering in ornamental potted plants. Findings indicate that lightweight growing mixtures, combining different media in optimal proportions, improve plant growth in containers. Studies have shown that chrysanthemum pot mum grown in cocopeat-based media can replace traditional soil. Orchids and lilies thrive best in cocopeat, enhancing vegetative growth, flower yield and quality. Anthurium's vegetative growth improves in sand and coir pith compost, while cocofiber, FYM and neemcake enhance its flowering.Vermicompost and coarse sand promote zinnia flower yield. Organic waste media, such as paddy straw compost and burnt rice husk, boost kalanchoe growth and flowering. Optimized growing media are crucial for successful ornamental crop production, impacting plant health, growth rates and quality. Alternatives to traditional soil include peat, coir, perlite, vermiculite, bark and synthetic substrates, each offering unique benefits in water retention, aeration and nutrient availability. Advances in sustainability incorporate biodegradable materials, waste products and biochar. These examples show how enhanced growing media can improve the efficiency and sustainability of ornamental crop production, addressing economic and environmental considerations. Thus, the choice of growing medium significantly affects the development and flowering of potted ornamental plants, adding value to their production.